2022
DOI: 10.21037/atm-22-1126
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia is associated with poor clinical outcomes in patients with inflammatory bowel disease: a prospective cohort study

Abstract: Background: Patients with inflammatory bowel disease (IBD) often have low weight, malnutrition and sarcopenia. The criteria of sarcopenia used were European and American standards previously. The aim of the study was to evaluate the impact of sarcopenia on clinical outcomes in patients with IBD using the Asian Working Group for Sarcopenia 2019 (AWGS2019) criteria. Methods:The inclusion of the subjects was IBD patients between 18 to 60 years. Sarcopenia, presarcopenia and sarcopenic obesity were defined. Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 41 publications
2
29
0
Order By: Relevance
“…In addition, study found that the sarcopenia group had higher surgery, re-hospitalization and death rate than the control group in patients with in ammatory bowel disease [24]. And, intensifying the dose of in iximab with LOR on standard dosing patterns can improve the mucosal healing rate [25].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, study found that the sarcopenia group had higher surgery, re-hospitalization and death rate than the control group in patients with in ammatory bowel disease [24]. And, intensifying the dose of in iximab with LOR on standard dosing patterns can improve the mucosal healing rate [25].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent retrospective study, sarcopenia was independently associated with increased risk of anastomotic leak in IBD patients undergoing colorectal surgery [32 ▪ ]. In a separate prospective study, sarcopenia, measured by grip strength and muscle mass in patients with IBD who were 18–60 years-old, was associated with worse clinical outcomes as compared to controls and individuals defined as presarcopenic [35 ▪ ]. Future research should expand upon this using uniform diagnostic criteria, and include measures of muscle strength and function to comprehensively evaluate the impact of sarcopenia on operative and clinical outcomes in IBD.…”
Section: Sarcopeniamentioning
confidence: 97%
“…Of interest, in the multivariate analysis, pre-operative nutritional optimization was protective (OR 0.13, p = 0.004) against surgical complications. 45 Most recently, Liu et al 46 utilised a prospective cohort study to better understand the impact of sarcopenia on clinical outcomes and similarly identified that those with sarcopenia (as defined by BIA and handgrip) and a normal BMI as well as those with sarcopenic obesity had higher rates of readmission and re-operation as well as post-operative mortality. Finally, a recent meta-analysis identified 4 studies that evaluated the impact of sarcopenia on post-operative complications in patients with IBD.…”
Section: Impact On Surgical Complicationsmentioning
confidence: 99%